Globalization and taste convergence: The cases of wine and beer - Joshua Aizenman; Eileen Brooks (University of California, Economics Department, 2005)
This paper investigates changes in cultural consumption patterns for a low-concentration industry: wine and beer. Using data on 38 countries from 1963-2000, there is clear convergence in the consumption of wine relative to beer between 1963 and 2000. Convergence occurs even more quickly within groups of countries that have a higher degree of integration. A key prediction of international trade is confirmed in the data: greater trade integration weakens the association between production and consumption patterns - although the relative consumption of wine can be explained well in 1963 by grape production and latitude, these variables are much less significant in 2000. Despite these "scientific" explanations for the consumption of wine, there is also a cultural angle to wine consumption. While the relative wine consumption of France and Germany is converging, several Latin American countries fail to converge. The patterns of convergence are consistent with dynamics of adjustment in an overlapping generation habit formation model.
Keywords: 330; convergence; globalization; trade and taste convergence; habit formation